What Primary School Teacher Trainees Know and Plan to Teach on the Concept of Matter. Study of the Amplitude, Diversity and Conceptual Organization [Lo Que Saben y Piensan Enseñar Los Futuros Profesores de Escuela Primaria Sobre el Concepto de Materia. Estudio de la Amplitud, Diversidad y Organización Conceptual] - Contreras-Palma, S; Gonzalez-Donoso, A (2013)
The disciplinary knowledge of 66 primary school trainee teachers has been investigated in relation to range, diversity, and conceptual organization for the teaching of the concept of "matter". An open-ended questionnaire was employed and a qualitative analysis of the data through maps of organization and conceptual distribution. The main results indicate that when the prospective teachers are questioned about the concept "matter" they a meager disciplinary knowledge. This poor knowledge is characterized by insufficient diversity, few conceptual relationships, difficulties in establishing microscopic level concepts and total absence of symbolic level concept. In other words they possess a reduced conceptual field.